Scenario-based projections of electricity prices in China’s carbon-neutral transition - Shurui Wang; Jianlei Mo; Jie Yang; Mingxi Liu; Jiaofeng Pan; Xunpeng Shi; Ye Huang (iScience)
Summary: China’s carbon neutrality goal by 2060 presents major challenges and opportunities for its electricity market. This study analyzes baseline, low-efficiency, and high-efficiency scenarios to represent potential decarbonization pathways in China up to 2060, aiming to estimate the range of electricity prices for each province. A comprehensive dataset covering 5680 coal power units, 342 hydroelectric plants, 172 gas power stations, 19 nuclear power stations, and various solar and wind farms, provides a solid foundation for a bottom-up calculation approach. The results show that most provinces will see a decline in electricity prices due to technological advancements and optimized power generation. The findings in this research contribute to the academic understanding of regional electricity market dynamics under long-term decarbonization scenarios and offer a quantitative basis for evaluating policy impacts on future electricity pricing.